MEMINIMUMKAN JUMLAH KALORI DI DALAM TUBUH DENGAN MEMPERHITUNGKAN ASUPAN MAKANAN DAN AKTIVITAS MENGGUNAKAN LINEAR PROGRAMMING - Lestari Dwi Asih; Maya Widyastiti (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2016)
Calorie is defined as a unit used to measure power or energy value. The calories in a food depends on the content of carbohydrates, protein, and fat in the food itself. Excess calories can lead to obesity disease and another diseases. So, it is important to know the amount of the calories in the body. In this study, to determine the number of calories needed by the body based on age, gender, height, weight and type of daily activity. The amount of calories that will be consumed as much as needed by the body and perform the activity as much as possible at certain time intervals to minimize the amount of calories in the body by considering the constraints that exist with using linear programming.Key words : Integer Linear Programming, Optimization, diet, foods and activities